Juguemos con la adición - Arevalo Pedraza, Eliseo (2020)
If we stop and visualize our present in the education sector we will realize that today's societies bring with us a series of limitations in terms of the development of skills, values, attitudes, abilities and competencies; which do not let us move forward as a country full of opportunities. One of which Peruvians have great difficulty is precisely in the competence of the area of Mathematics in their competition solves quantity problems._x000D_ It is because of the above that in the present learning strategy the game has been shaped as a strategy for students to learn all about addition as a main method, not only to improve cognitive, communicative ability; but also that the students are protagonists of the development of their own knowledge, thus consolidating the teacher as a mediating agent._x000D_ On the other hand, the present work is based on theorists and pedagogues who give us their input on the game, the addition, pedagogical and didactic processes, materials, evaluation, meta cognition and other sub contents that are closely related to this Learning strategy. They also offer us a range of orientations on how the educational process should be developed with children of all levels and educational cycles.